Methotrexate withdrawal in patients with rheumatoid arthritis who achieve low disease activity with tofacitinib modified-release 11 mg once daily plus methotrexate (ORAL Shift): a randomised, phase 3b/4, non-inferiority trial. (September 2019) - Cohen, Stanley B; Pope, Janet; Haraoui, Boulos; Irazoque-Palazuelos, Fedra; Korkosz, Mariusz; Diehl, Annette; Rivas, Jose L; Lukic, Tatjana; Liu, Shixue; Stockert, Lori; Iikuni, Noriko; Keystone, Edward C
Summary: Background: Tofacitinib is an oral Janus kinase (JAK) inhibitor used for the treatment of rheumatoid arthritis. We assessed the efficacy and safety of tofacitinib after methotrexate withdrawal in patients who achieved low disease activity (LDA) with tofacitinib in combination with methotrexate. Methods: ORAL Shift was a phase 3b/4 non-inferiority trial in patients aged at least 18 years with moderate-to-severe rheumatoid arthritis and an inadequate response to methotrexate done in 109 centres across 16 countries. After 24 weeks of open-label tofacitinib modified-release 11 mg once daily plus methotrexate, patients who achieved LDA (clinical disease activity index [CDAI] ≤10) were randomly assigned 1:1 via an automated web-based response system to receive tofacitinib plus placebo (tofacitinib monotherapy; ie, masked methotrexate withdrawal) or continue tofacitinib plus methotrexate for 24 weeks in a double-blind manner. The primary endpoint was the least squares mean change from week 24 to week 48 in disease activity score in 28 joints with four variables, including erythrocyte sedimentation rate (DAS28-4[ESR]). The primary analysis was done in all patients who received at least one dose of study treatment in both phases, and safety was assessed in all patients who received at least one dose of study treatment since enrolment. Non-inferiority of tofacitinib monotherapy versus tofacitinib plus methotrexate was declared if the upper bound of the 95% CI for the difference in change in DAS28-4(ESR) between treatment groups was less than 0·6. Safety was assessed in both phases. The trial is registered with ClinicalTrials.gov, NCT02831855, and is complete. Findings: Between Sept 1, 2016, and Nov 1, 2017, 694 patients were enrolled in the open-label phase and 623 received study treatment for 24 weeks. 533 achieved CDAI-defined LDA and were randomly assigned into the double-blind phase (267 in the tofacitinib monotherapy group and 266 in the tofacitinib plus methotrexate group). Three participants in the monotherapy group did not start treatment so were not included in the primary analysis. Non-inferiority was demonstrated (difference 0·30 [95% CI 0·12–0·48]). 107 (41%) of 264 patients in the tofacitinib monotherapy group and 109 (41%) of 266 in the tofacitinib plus methotrexate group had adverse events; five patients from each group discontinued because of adverse events; two patients died in the tofacitinib plus methotrexate group. No new safety findings were reported up to 48 weeks. Interpretation: Patients with rheumatoid arthritis who achieve LDA with a combination of tofacitinib plus methotrexate may consider withdrawing methotrexate without significant worsening of disease activity or unexpected safety issues. Funding: Pfizer.